Τα κόμικς : Σούπερμαν, Αστερίξ, Τεν Τεν, Φλας Γκόρντον, Ποπάυ, Ταρζάν, Κόναν, Κόρτο Μαλτέζε - Κολιοδήμος, Δημήτρης; Σολδάτος, Γιάννης, 1952- (Λογοτεχνικά κείμενα και θεωρία, 1982)
Σούπερμαν, Αστερίξ, Τεν Τεν, Φλας Γκόρντον, Ποπάυ, Ταρζάν, Κόναν, Κόρτο Μαλτέζε.